Design and verification of a tool to automate test procedures for autonomous emergency braking systems - Song, He (My University, 2019)
A large number of road crashes are caused by late braking due to distraction, inattention, poor visibility, or other unexpected situations. It is difficult for most drivers to deal with such critical situations and react in time to avoid a crash. AEB systems are now widely used to help the driver avoid such accidents or at least reduce their severity. However, before AEB systems’ introduction to the market, their performances need to be verified in test-track for certification purposes. Within this thesis, a tool to automate test procedures for AEB systems was designed using a MATLAB GUI. The aim of this tool is to improve test efficiency by providing timely feedback to the test engineers about the outcome of a test. The waterfall model was used to design and verify the tool. The requirements for the tool were collected from the future users of the tool. The algorithm and interface design were then performed for the tool based on the collected requirements. After implementation of the code, the tool was verified at different levels to validate its effectiveness. The results from the tool technical and acceptance tests show that the tool successfully fulfilled all the user requirements. The tool interface is user-friendly and the tool is also robust enough to evaluate testing results for various test cases.
Keywords: Active safety; MATLAB GUI; Legal requirements; Track testing; Waterfall model; Software development; Software testing